CARDIOPULMONARY RESUSCITATION COUNSELING ON STUDENTS’ KNOWLEDGE LEVEL AND ATTITUDE IN SMK KESEHATAN SAKINAH KOTA PASURUAN - Rochmah, Pribadi Auni; Roni, Faishol; Santoso, Shelfi Dwi Retnani Putri (LPPM STIKes Bahrul Ulum Jombang, 2019)
Out-of-Hospital Cardiac Arrest (OHCA) becomes a central focus of global health issues since the mortality rate is very high. Cardiac arrest can occur in various locations, both in which can not be anticipated (out of hospital) and can be anticipated (for instance: Intensive Care Unit Room). Knowledge level is very essential because with it, the attitude that is reflected in them will be in accordance with the knowledge gained. This research aims to study the impacts of cardiopulmonary resuscitation counseling on students knowledge level and attitude in SMK Kesehatan Sakinah Kota Pasuruan. Using Quasi-Eksperimental design with applying the approach of one - group pre - post test design. The samples are 30 students of SMK Kesehatan Sakinah Kota Pasuruan. using the technique of total population sampling. The data were collected using questionnaire. The obtained results showed that the level of knowledge in the category of low-level was 23 respondents (76.7%) and the attitudes in the category of low-level were 16 respondents (53.3%). After the results were tested using Wilcoxon Test, obtained = 0.000 where p <0.005 In conclusion, cardiopulmonary resuscitation affected the students knowledge level and attitude in SMK Kesehatan Sakinah Kota Pasuruan. To improve the students knowledge level and attitude, accordingly following cardiopulmonary resuscitation may be worked. Keywords: cardiopulmonary resuscitation counseling; knowledge level; attitude